Pioneering and Upgrading the Postgraduate Research and Training: Role of RTMD of Bangladesh College of Physicians and Surgeons - Md Jamal, Abul Bashar; Arafat, Shohael Mahmud; Islam, Ferdousi; Chowdhury, Md Fazle Rabbi; Parvin, Tabassum; Ali Kawser, Choudhury (Journal of Bangladesh College of Physicians and Surgeons, 2022)
The Research and Training Monitoring Department (RTMD) has been playing an important role in research and training activities. RTMD is designed to enhance the qualities of clinical training, research skills and the development of other soft skills of post graduate trainees of different faculties. RTMD monitors the training of doctors who will appear in the fellowship examination in various disciplines. It is also involved in the timely evaluation of research activities of health professionals in this field. The core activities of the department are now not only confined to the training and research, but it extends it’s wing to help the trainees technically by Research clinic and financially by the handsome research grants. Time to time updating of training manual by different modern tools by the department is also appreciating. Here the important activities of the RTMD are being highlighted in its all aspects. J Bangladesh Coll Phys Surg 2022; 40: 57-61